Designing evaluation plans for health promotion mHealth interventions: a case study of the Milk Man mobile app - White, B.; Burns, S.; Giglia, R.; Scott, Jane (Australian Health Promotion Association, 2016)
Evaluating complex health promotion interventions that use mobile apps requires comprehensive and adaptive evaluation plans. As mobile usage becomes increasingly sophisticated and personalised, broad evaluation plans are important in determining the impact and efficacy of a mobile health (mHealth) app. Evaluation should consider user feedback and outcome measures, as well as examine elements such as the robustness of the technology, the intervention principles and engagement strategies, and the interaction of the user with the technology. This paper introduces four mHealth evaluation models and tools and describes the evaluation plan that has been developed for Milk Man, a breastfeeding app targeting new and expectant fathers. Milk Man is a socially connected, gamified app that is being tested in a large Randomised Control Trial (RCT). While there is a need for mobile apps to be evaluated in adequately powered RCTs, trialling mobile apps over a long period of time presents challenges. Incorporating robust evaluation design will help ensure that technological performance, app intervention principles, as well as health and behavioural outcomes are measured. The detail and scope of the Milk Man app evaluation plan will ensure the findings add to the evidence base and have broad relevance to health promotion practitioners.So what? Evidence about the efficacy of mHealth interventions is an emerging area and appropriate evaluation skills are needed. This paper illustrates an evaluation planning approach for mHealth interventions that could be adapted for use by health promotion practitioners and researchers.